Ewolucja struktur nadzoru nad rynkiem finansowym Unii Europejskiej - rozwiązania przejściowe - Kurek, Robert (The evolution of supervision structures over the EU financial market - temporary solutions, 2007)
The supervision structures over financial sector actors based on sector and national approach were "modern'' at the time of creating a homogenous European Union market. Transformations al financial market have forced new solutions on the EU regulatory bodies and have taken the form of consolidated supervision - the directive on complementary supervision and lead supervision (CRD Directive) considering its above national and partly a cross-sector nature, however, only with reference to banks and other credit institutions. The concept of Lead Supervisor becomes the reaction of financial market actors to the occurring transformations which takes the supervision structures of above national and above sector type into account. The introduced solutions and suggestions constitute only a temporary stage aiming at an overall integration of the supervision structures.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 122-132